AN ANALYSIS OF THE RELATIONSHIP BETWEEN HUMAN AND NONHUMAN USING ECOCRITICISM IN GORDEN J.L RAMEL’S POEMS - Manalu Yerico Calvin; Singgih Daru Kuncara; Fatimah Muhajir (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
The research aims to analyze the relationship between human and nonhuman and representation of nature in Gorden J.L Ramel’s Poems entitled “Mankind Doesn’t Agree”, “Tiger Tiger Revisited”, and “Daffodils No More”. This research used qualitative method and ecocriticism theory by Greg Garrard. There are two concepts of ecoriticism that were used by the researcher. The concepts of animals and pastoral were used to analyze the relationship between human and nonhuman and the representation of nature in the poems. The results of this research are human should not do abusive or disruptive actions as the concept of animals mentioned like human and animals should have a good relationship which means human should treat animals well. Moreover, the concept of pastoral states human and nature should have a harmony relationship which means the existence of nature should be stable as the counter of disruptive energy and change of human societies. The implication of this research the other researchers can use the other concepts of ecocriticism by Garrard Greg to analyze their research object likes a poem that discuss about nature and also other literary works.